2022
DOI: 10.3389/ijph.2022.1604395
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Mental Health and Lifestyle Behaviour During the COVID-19 Pandemic in the Czech Population: Evidence From Two Cross-Sectional Surveys

Abstract: Objectives: Evidence of the impact of COVID-19 pandemic on mental and physical health behaviours is limited. This study presents results of two cross-sectional surveys on mental health changes and its consequences on healthy and unhealthy lifestyle behaviours.Methods: An online survey was distributed during Spring 2020 (N = 9,168) and Autumn 2020 (N = 1,042) in the Czech Republic. Differences in mental health observed in both surveys were evaluated using Mann-Whitney test and logistic regressions were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(54 reference statements)
1
1
1
Order By: Relevance
“…We found that the magnitude of mental health changes varied by sociodemographic characteristics. Contrary to previous European research suggesting that older adults cope with the COVID-19 crisis better than younger individuals,23 29–31 our study showed that changes in depression scores were strongly associated with age; the highest depression changes were observed in the oldest age group (≥76 years) of the participants compared with younger individuals. This could be explained by the exacerbated fear of becoming severely ill or dying for COVID-19 with increasing age.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that the magnitude of mental health changes varied by sociodemographic characteristics. Contrary to previous European research suggesting that older adults cope with the COVID-19 crisis better than younger individuals,23 29–31 our study showed that changes in depression scores were strongly associated with age; the highest depression changes were observed in the oldest age group (≥76 years) of the participants compared with younger individuals. This could be explained by the exacerbated fear of becoming severely ill or dying for COVID-19 with increasing age.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, depression and pandemic-related stressors were measured before the vaccination was available, which could cause much higher stress and anxiety. In addition, this study provides only several potential pandemic-related risk factors of depressive symptoms (eg, social isolation, financial distress, death or hospitalisation of a close person) while current literature highlighted also the importance of personality characteristics and lifestyle (eg, sleep quality, physical activity etc) that might play an important role in mental health changes 7 17 31. Lastly, reverse causation bias, a pervasive issue in observational studies, might occur.…”
Section: Discussionmentioning
confidence: 97%
“…In Switzerland, evidence suggests that the mental health status of the majority of the population has not been severely affected by the pandemic, but that young people and especially young females have been particularly vulnerable to the detrimental mental health effects of the pandemic [7,8]. These findings are well in line with the international literature [9][10][11][12][13][14].…”
Section: Introductionsupporting
confidence: 66%